Behind the Shipment: Unpacking Corporate Criminal Liability in the PT. Shippindo Logistics Case - Efanof, Riandhy Mufti; Arifin, Ridwan (Law Research Review Quarterly, 2025)
The growth of Indonesia’s logistics industry has significantly streamlined the distribution of goods, both domestically and internationally. However, alongside these advancements, there is an increasing risk of misuse of logistics services for illegal activities, such as the smuggling of narcotics, unauthorized firearms, and other prohibited items. PT. Shippindo Teknologi Logistik, as one of the logistics service providers operating within Indonesia’s vast and complex geography, faces particular vulnerability to such illicit practices. In this context, logistics companies are expected to implement due diligence in every shipping transaction to prevent involvement in criminal activities. This study aims to analyze the construction of corporate criminal liability under the Indonesian legal system, particularly in relation to the alleged involvement of PT. Shippindo Teknologi Logistik in the shipment of illegal goods. Additionally, the research evaluates the effectiveness of law enforcement in similar cases within the logistics sector. The method employed is normative legal research using a descriptive approach, relying on secondary data such as legal theories, concepts, and relevant legislation. The findings indicate that a corporation can be held criminally liable if it is proven to have committed or allowed a criminal act to occur due to negligence or failure within its management system. In the case of PT. Shippindo Teknologi Logistik, criminal liability may be imposed if systemic negligence or willful disregard for suspicious activities in its operations can be demonstrated. While Indonesia’s legal framework does provide the basis for prosecuting corporate entities, enforcement in practice faces several challenges, particularly in proving fault and ensuring coordination among law enforcement agencies. Therefore, it is essential to strengthen regulations and ensure stricter implementation of compliance and due diligence principles, especially for logistics providers engaged in cross-border trade.